(untitled) (TEST XY. Critical review of studies on the representation of architecture and use of the image in science and art, 2019)
This article provides an opportunity to explore some important cases of a study, started but open to further contributions, on the engraving architects of the twentieth century, whose products deserve to be catalogued and read, because they are neglected pieces of a cultural moment which in other aspects is significantly debated. The engraving production of the Italian architects of the late twentieth century is in fact a little–investigated area, but is of considerable interest for contemporary architectural culture, for the meaning given to the application of that particular artistic practice, and for the importance of the personalities who have dedicated themselves to it: Alessandro Anselmi, Carlo Aymonino, Mario Botta, Arduino Cantàfora, Giangi D’Ardia, Paola D’Ercole, Costantino Dardi, Vittorio De Feo, Vittorio Introini, Paolo Martellotti, Massimo Martini, Alessandro Mendini, Giovanni Michelucci, Bruno Minardi, Dario Passi, Franco Pierluisi, Paolo Portoghesi, Franz Prati, Franco Purini, Aldo Rossi, Massimo Scolari. The article examines the experimentations of architects such as Aldo Rossi, Arduino Cantàfora, Giovanni Michelucci and Franco Purini, but above all the focus is on the existence of the original matrices, at risk of degradation and dispersion, in the face of a lack of identification and underestimation of this particular strand of architecture drawing culture.